Synthesis of Magic Adsorbent Pipe (MAP) Utilizing Rice Husk, Coconut Shell and Coal Fly Ash as an Effort to Purify Water - Dini Novi Rohmah; Siti Khuzaimah; Arina Manasikana (Jurnal Ilmiah Teknik Kimia, 2023)
The existence of water for the life of living things on this earth is very vital, humans in daily life need clean water for consumption, self-cleaning, farming, and other activities. Cilacap has many industries, where many industries bring waste to the waters. The method used for MAP (Magic Adsorbent Pipe) is by coagulating 50 g of rice husk and 50 g of coconut shell, then adding 100 g of coal fly ash, and then making pipe briquettes were made using the addition of aci flour adhesive. After that, the MAP pipes containing 3 kinds of adsorbents were tested for quality by color, pH, BOD, and COD tests. The air tends to be alkaline with a pH of 8 and becomes neutral with a pH of 7. Then the BOD also decreased from 7,442 mg/L to 6,363 mg/L and the amount of COD from 11,107 mg/L to 9,497 mg/L.